Taxonomy of Atlantic Central African orchids 3. A new species of Bulbophyllum Thouars (Orchidaceae) from the Monts de Cristal, Gabon - Stévart, Tariq; Biteau, Jean Philippe; Cawoy, Valérie; Droissart, Vincent (Phytotaxa, 2014)
Two specimens of an apparently new Bulbophylum species were found in the Monts de Cristal, Gabon. They have a unique leaf shape among the species of this genus in Continental Africa. The flower shares the general morphology of Bulbophyllum saltatorium, one of the most common members of Bulbophyllum in Central Africa. Eight other taxa of the Continental African Bulbophyllum possess unifoliate pseudobulbs and long hairs on the lip. Comparison with them indicates that the new collections from Gabon represent a distinctive species, not yet known in the genus. We describe it here as Bulbophyllum pauwelsianum. The distinguishing features of the species include its leaves, which are pendant, coriaceous, linear, semiterete and v-shaped in transverse section, and its sepals, which possess relatively long hairs on their margins. A table of the taxonomic treatments of the nine Continental African Bulbophyllum taxa considered here is included. A taxonomic key and a table of the diagnostic characters of these nine taxa are given to facilitate identification. The new species is restricted to lowland forests of the Monts de Cristal in Gabon. A preliminary assessment of the conservation status, using the IUCN Red List Categories and Criteria is provided.